The effect of psychological capital and trust on organizational citizenship behavior among academic in Malaysian Universities - Chan, Wing Yee; Chia, Yee Teng; Liew, Shang Yeong; Lok, Wei Xin (2021)
In the context of the COVID-19 pandemic, various industries have been affected, and universities are inevitable. The impact has been shown in the tremendous changes in the academic’s working mode. These changes require academics to adopt the new teaching or working mode rapidly to deal with students and university. However, this challenging task and process will indirectly affect the academics performance and extra-role behaviour. Hence, this research intends to examine the effect of psychological capital (PsyCap) and trust on the Organisational Citizenship Behaviour (OCB) among the academics in Malaysia universities. PsyCap included four dimensions namely: self-efficacy, optimism, resilience, and hope. In this research, a quantitative approach was applied, with a sample size of 65 academics from five public and five private universities located in Malaysia. Moreover, Cronbach’s Alpha model and Multiple Regression Analysis was used to examine the relationship between independent variables and dependent variables. Furthermore, Statistical Package for the Social Sciences (SPSS) was used in this research to analyze all the data that was collected from the respondent.